Experiences of registered nurses caring for patients with an open abdomen in an intensive care unit in Gauteng - Mpho G. Chipu; Irene Kearns; Wanda E. Nel (AOSIS, 2017)
The researcher observed that nurses prefer not to nurse patients with an open abdomen as they fear that the abdominal contents will protrude. The purpose of the study was to explore and describe the experiences of registered nurses taking care of patients with an open abdomen in intensive care in an academic hospital in Gauteng, and to provide recommendations for registered nurses when taking care of patients with an open abdomen. The research design used was a qualitative, exploratory, descriptive and contextual design. Focus group interviews were conducted with each group comprising six participants. The research question was: What are the experiences of registered nurses caring for patients with an open abdomen in an intensive care unit? What recommendations can be made to assist registered nurses in taking care of patients with an open abdomen in an intensive care unit? The data was analysed using Tesch's method. Three themes emerged: Difficulty in nursing care, complications such as fistula and infections, and poor hospital administration. Recommendations for assisting registered nurses in taking care of patients with an open abdomen were then made based on the findings of the four focus group interviews. Ethical principles and measures of trustworthiness were adhered to throughout the research study.